Development Of Archives Using Sequential Searching Algorithms In Design Department Politeknik Negeri Media Kreatif - Supiyanti, Tri Fajar Yurmama; Nurrahmi, Herly; Suhaili, Muhammad (Devotion : Journal of Research and Community Service, 2022)
The quality of service in each organization is one indicator of the success of a business entity or organization. In meeting these indicators, information systems or information applications are a mainstay in a business strategy. In several departments or faculties at various universities, the business process that is often carried out is archive management. Archiving activities are very important because they involve official documents and are important for every institution. Increased technological innovation has empowered institutions to monitor archives in a digital way. The purpose of this research is to create a website-based archive application using sequential searching algorithms that can be used to record and store easily and safely, and be managering every archive for essier access. The system development methodology uses the waterfall method and the PHP and MySQL programming languages. This application can be used to record, store, display archives by category and can be used to display archives by category, preview archives, download archives and archive details in the Design Department of the Polytechnic Media Creative.